2022
DOI: 10.3390/biology11060939
|View full text |Cite
|
Sign up to set email alerts
|

The Inflammatory Response after Moderate Contusion Spinal Cord Injury: A Time Study

Abstract: Spinal cord injury (SCI) initiates detrimental cellular and molecular events that lead to acute and delayed neuroinflammation. Understanding the role of the inflammatory response in SCI requires insight into the temporal and cellular synthesis of inflammatory mediators. We subjected C57BL/6J mice to SCI and investigated inflammatory reactions. We examined activation, recruitment, and polarization of microglia and infiltrating immune cells, focusing specifically on tumor necrosis factor (TNF) and its receptors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 85 publications
5
22
0
Order By: Relevance
“…The locomotion is affected by the SCI in mice. This result was similar to those of previous SCI studies, which included either a SCI induced by the occlusion of the aorta, for a brief amount of time, or a SCI induced by contusions in mice [24,25].…”
Section: Discussionsupporting
confidence: 89%
“…The locomotion is affected by the SCI in mice. This result was similar to those of previous SCI studies, which included either a SCI induced by the occlusion of the aorta, for a brief amount of time, or a SCI induced by contusions in mice [24,25].…”
Section: Discussionsupporting
confidence: 89%
“…Diminishing the robust neuroinflammatory response and the detrimental immune signaling could reduce tissue damage and accelerate functional recovery following SCI [30]. In line with these findings, HMGB2 knockdown inhibited SCI-induced microglial activation.…”
Section: Discussionsupporting
confidence: 60%
“…A recent study indicated that suppressing microglia-mediated neuroinflammation was a potential therapeutic strategy for neuropathic pain in the spinal cord of mice [ 29 ]. Diminishing the robust neuroinflammatory response and the detrimental immune signaling could reduce tissue damage and accelerate functional recovery following SCI [ 30 ]. In line with these findings, HMGB2 knockdown inhibited SCI-induced microglial activation.…”
Section: Discussionmentioning
confidence: 99%
“…The initial traumatic event, or primary injury, is followed by several biological events termed the secondary injury. There are, however, three pathological stages that define the secondary injury in SCI: the acute phase (48 h), subacute phase (2–14 days), and chronic phase (more than 6 months) 4 7 .…”
Section: Sci Pathophysiologymentioning
confidence: 99%